Unmet needs in psoriatic arthritis, a narrative review - Clementina Lopez-Medina; Umut Kalyoncu; Laure Gossec (Archives of Rheumatology, 2024)
Psoriatic arthritis is a chronic rheumatic disease that poses challenges in its diagnosis, evaluation, and management. The heterogeneity in the manifestations and the absence of definitive diagnosis biomarkers often complicates the process of accurate diagnosis. Furthermore, the involvement of multiple disease domains poses difficulties in assessing disease activity and defining the concept of remission. Despite therapeutic advancements, a subset of patients remains refractory to treatment, leading to the emergence of the concept of “difficult-to-treat” patients and the necessity for novel therapeutic approaches (e.g., drugs with novel mechanisms of action; combinations of treatments). This review addresses key unmet needs in psoriatic arthritis, in terms of diagnosis, classification, evaluation, comorbidities and treatment.